2013
DOI: 10.1038/aja.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Can DNA fragmentation of neat or swim-up spermatozoa be used to predict pregnancy following ICSI of fertile oocyte donors?

Abstract: This study compared the potential of assessing sperm DNA fragmentation (SDF) from neat semen and the subsequent swim-up (SU) procedure to predict pregnancy when conducting ICSI of fertile donor oocytes. Infertile females (n581) were transferred embryos resulting from intracytoplasmic sperm injection (ICSI) of their partner's spermatozoa and proven donor oocytes. This model normalized the impact of female factor in putative sperm DNA repair. Semen was blindly assessed for SDF using Halosperm immediately followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Similar result was reported in a study comparing DNA fragmentation of neat and swim-up spermatozoa to predict pregnancy following ICSI. The cut-off value of the neat spermatozoa that resulted in 80% of pregnancy rate was 26% [ 30 ]. There are only a few published papers that specifically used SCD test (or Halosperm test) to assess male infertility and reported the correlation with IVF or ICSI outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar result was reported in a study comparing DNA fragmentation of neat and swim-up spermatozoa to predict pregnancy following ICSI. The cut-off value of the neat spermatozoa that resulted in 80% of pregnancy rate was 26% [ 30 ]. There are only a few published papers that specifically used SCD test (or Halosperm test) to assess male infertility and reported the correlation with IVF or ICSI outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to studies on fertility, this technique has been applied to different clinical and toxicological situations such as varicocele,32 ejaculatory abstinence,33 cigarette smoking and alcohol consumption,34 and genitourinary infection 35. From SCD criteria, independently of the test kit used, sperm cells with very small halos or without halos, as well as degraded sperm cells, are classified as containing fragmented DNA, and cells with intermediate or large halos are not considered fragmented 20222936. In some papers, the description is somewhat more accurate, including references to relatives sizes, but proper morphometric measures have not been done 37…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, if oocyte quality can be somehow homogenised or standardised, using for example donor oocytes, then it may be more likely to elucidate a stronger relationship between high levels of baseline SDF and reduced pregnancy rate [19]. There are numerous studies that have shown that the oocyte has the capacity to repair sperm DNA damage [20][21][22].…”
Section: Discussionmentioning
confidence: 99%